High intake of dietary advanced glycation end-products is associated with increased arterial stiffness and inflammation in subjects with type 2 diabetes - Di Pino, A.; Currenti, W.; Urbano, F.; Scicali, R.; Piro, S.; Purrello, F.; Rabuazzo, A.M. (Nutrition, metabolism, and cardiovascular diseases, 2017)
Modern diets are high in advanced glycation end-products (dAGEs), derived from processing methods, exerting a pivotal role in promoting atherosclerotic risk. In this cross-sectional study we investigate the relationship between dAGE intake, arterial stiffness, inflammatory profile and macronutrient composition, in subjects with type 2 diabetes without overt cardiovascular disease. Arterial stiffness, carboxy-methyl-lysine, endogenous secretory receptor for AGEs (esRAGE), high sensitivity C reactive protein (hs-CRP), S100A12 and macronutrient intake were evaluated in 85 subjects with type 2 diabetes. The subjects were stratified into two groups according to dAGE consumption: high and low dAGE intake (≥ or <15.000 kU/day, respectively). Subjects with high dAGE intake (n = 45) showed a higher augmentation, augmentation index and pulse wave velocity (PWV) compared with those subjects with low dAGE intake (18 ± 5.4 vs 12.2 ± 6.3 mmHg, P < 0.05; 38.3 ± 5.4 vs 29.3 ± 10%; 9.2 ± 1.4 m/sec vs 7.9 ± 1.7, P < 0.05, respectively). hs-CRP were higher in subjects with high dAGE intake [0.42 (0.18–0.54) vs 0.21 (0.14–0.52) mg/dL, P < 0.05] whereas esRAGE plasma levels were lower [0.16 (0.23–0.81) vs 0.2 (0.14–0.54) ng/dL, P < 0.05]. Simple regression analysis showed a correlation between dAGEs and fat intake. Multivariate analysis showed an independent association between augmentation, systolic blood pressure (BP) and dAGE consumption; BMI and esRAGE were the major determinants of PWV. Our data suggests that a chronic high dAGE diet could lead to a vascular dysfunction and inflammatory activation, contributing to the development of vascular complications in subjects with type 2 diabetes. Testing this hypothesis may represent a direction of future research. •We studied dAGEs intake and cardiovascular risk in subjects with type 2 diabetes.•Subjects with high dAGEs intake had high arterial stiffness and inflammatory markers.•Arterial stiffness was independently associated with dAGEs in multivariate analysis.•Simple regression analysis evidenced a correlation between dAGEs and fat intake.•Subjects with diabetes and high dAGEs intake have increased cardiovascular risk.